TANGGUNG JAWAB KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) SAMARINDA TERHADAP PENYELESAIAN PIUTANG MACET TANPA JAMINAN - Gatot Wijanarko (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTThe problem in this study is the responsibility of Samarinda State Wealth and Auction Service Office in the management and settlement of government bad debts and the purpose of this study is to find out how the role of KPKNL Samarinda in managing and settling government bad debts and the extent of the settlement process and what obstacles it faces.The method used in this study is an empirical juridical approach and uses descriptive analysis techniques. This is used to see KPKNL in carrying out its roles and responsibilities in completing bad debts of the government as tasks and functions contained in the law. Keywords : Role of KPKNL, Responsibility, Receivables, Government